The Role of Insecurity in Shaping Consumer Purchase Intentions: Mediating Effects of Perceived Usefulness and Ease of Use in Live Commerce - Wicaksono, Teguh; Ariani, Gusti Meinar Girda; Syahrani, Syahrani; Royanti, Farhana; Gina, Wardatul (RSF Conference Series: Business, Management and Social Sciences, 2024)
Live commerce platforms facilitate real-time interactions between sellers and buyers, but challenges related to consumer uncertainty can negatively impact their intention to purchase. This study examines how uncertainty affects perceptions of usefulness, ease of use, and the intention to purchase. Additionally, it investigates whether perceived usefulness and ease of use serve as mediators in these relationships. The research adopts a quantitative methodology, collecting data from 150 respondents in Banjarmasin using a questionnaire based on a 5-point Likert scale. The analysis employed Structural Equation Modeling with Partial Least Squares (PLS-SEM) to understand the interrelations among the variables. The findings reveal that insecurity does not significantly impact perceived usefulness, ease of use, or purchase intention, and these perceptions do not act as mediators in the relationship. However, both perceived ease of use and perceived usefulness have a strong and positive effect on purchase intention. These results underscore the need to focus on technology’s ease of use and functionality to encourage purchasing behaviour, even when insecurity is present. This suggests that e-commerce businesses should improve their platforms’ functional aspects and user-friendliness to enhance consumer engagement. Furthermore, the study encourages future research to delve into more profound psychological aspects and beliefs surrounding consumer insecurity that may influence decision-making in live commerce environments.